Previous vaginal birth twice cesareada. Hospital San Bartolomé - De la Vega, Guillermo (2015)
We present three cases of pregnant women each with history of two previous cesarean sections to whom we offered trial of labor. Following patient’s informed consent, we considered type of previous cesarean section, indications and contraindications for trial of labor, as well as early and late neonatal development care.